Metal-Metal Bonding - Parkin, Gerard (Structure and Bonding, 2010)
John Berry: Metal-Metal Bonds in Chains of Three or More Metal Atoms: From Homometallic to Heterometallic Chains.- Malcolm Chisholm: Electronically Coupled MM Quadruple Bonded Complexes of Molybdenum and Tungsten.- Philip Power: Transition Metal Complexes Stabilized by Bulky Terphenyl Ligands: Applications to Metal-Metal Bonded Compounds.- Gerard Parkin: Metal-Metal Bonding in Bridging Hydride and Alkyl Compounds.- Roland Fischer and Gernot Frenking: Structure and Bonding of Metal Rich Coordination Compounds Containing Low Valent Ga(I) and Zn(I) Ligands.- Mike Hill: Homocatenation of Metal and Metalloid Main Group Elements.- Constandinos A. Tsipis: Aromaticity/Antiaromaticity in "Bare" and ''Ligand-Stabilized'' Rings of Metal Atoms.- Alexander Boldyrev: All-Transition Metal Aromaticity and Antiaromaticity.